The effect of TNF treatment uptake on incident hospital admission in Western Australia - Erin Kelty; Ebony Quintrell; David B. Preen; Prue Manners; Johannes Nossent (BMC, 2023)
Abstract Objective Treatment strategies for juvenile idiopathic arthritis (JIA) have shifted significantly over the last 20 years. We examined the effect of the introduction of government-subsidised TNF inhibitor (TNFi) treatment on incident hospitalisation for JIA. Methods Western Australian (WA) hospital data were used to identify patients < 16 years hospitalised with JIA between 1990 and 2012. Changes in the number of patients with an incident hospitalisation, overall admissions and admissions for joint aspiration were examined using join-point regression TNFi dispensing data from 2002-2012 was used to describe defined daily doses (DDD)/1000 population/day. Results We included 786 patients (59.2% girls, median age 8 years) with a first-time admission with JIA. The annual incident admission rate was 7.9 per 100,000 person-years (95%CI: 7.3, 8.4) which did not change significantly between 1990 and 2012 (annual percentage change (APC): 1.3, 95%CI: -0.3, 2.8). Annual hospital-based prevalence of JIA reached 0.72/1000 in 2012. DDD for TNFi usage rose steadily from 2003 indicating TNFi usage by 1/2700 children in 2012, while overall admission rates (APC 3.7; 95%CI: 2.3, 5.1) and admission rates for joint injections (APC 4.9%; 95%CI: 3.8, 6.0) also increased significantly in that period. Conclusion Incident inpatient admission rates for JIA were stable over a 22-year period. The uptake of TNFi was not associated with lower admission rates for JIA, due mainly to an increase in admissions for joint injection. These results indicate a notable but unexpected change in hospital-based management of JIA since the introduction of TNFi therapy in WA, where hospital-based prevalence of JIA is slightly higher than in North America.